IFN-β therapy rescues dysregulated IFN-stimulated proteins, serum cytokines, and neurotrophic factors in multiple sclerosis: Multiplex analysis of short-term and long-term IFN responses - Lei Li; Maya Olcer; Zhe Wang; Yaerin Song; Jeffrey Ke; Xuan Feng; Anthony T. Reder (PLoS ONE, 2025)
Introduction Dysfunctional regulatory T cells and subnormal responses to interferon-β disrupt the immune system in multiple sclerosis. We probed dysregulated type I IFN pathways in vitro and in vivo IFN-β to induce transcription factors, cytokines, and neurotrophic factors. Methods 36 MS-relevant serum proteins curated to be relevant to MS were detected with multiplex and IFN activity assays plus western blots of mononuclear cells from 15 partial responders (PR) to IFN-β therapy with exacerbations over five years of treatment, and 12 clinical responders (CR) without exacerbations. Response was measured 0, 4, and 24 hours after injection of 16 million units (MU) of IFN-β (double-dose) and 8 MU (standard dose), in clinically stable PR and CR, and 16 MU IFN-β in paired PR during exacerbations, an IFN-resistant state. IFN-β effects after therapy washout were compared to 15 therapy-naïve stable and 13 active RRMS and 18 healthy controls (HC). Results IFN-β injection corrected subnormal levels of p-S-STAT1 transcription factor and induced antiviral MxA and type I IFNs. IFN-β induced anti-inflammatory IL-4, IL-10, IL-12p40, and TNFRII more strongly in stable PR than CR. Th2 cytokines correlated with serum vitamin D levels in CR. During exacerbations, IFN-β injections induced Th1, Th2, and neurotropic proteins. After therapy washout, serum IFN-α/β and pro-inflammatory IL-12p70 levels were lower in stable CR than in PR. In therapy-naïve MS, Th1, Th2, and neurotrophic protein levels were surprisingly subnormal and poorly intercorrelated. Long-term IFN-β therapy elevated serum proteins and brought them to a balanced positively-correlated state, echoing HC. Conclusions IFN-β corrects low serum type I IFN levels, enhances responses to subsequent IFN exposure, induces immunoregulatory and neuroprotective proteins, and balances dysregulated and subnormal serum cytokine levels. Low serum IFN and IFN-β-induced proteins link to better long-term response to IFN-β therapy. Correction of immune disruption suggests new mechanisms for immunopathology and therapy.